2000
DOI: 10.1126/science.287.5452.495
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Histone Acetylation in the Developmental Regulation of V(D)J Recombination

Abstract: VDJ recombination is developmentally regulated in vivo by enhancer-dependent changes in the accessibility of chromosomal recombination signal sequences to the recombinase, but the molecular nature of these changes is unknown. Here histone H3 acetylation was measured along versions of a transgenic VDJ recombination reporter and the endogenous T cell receptor alpha/delta locus. Enhancer activity was shown to impart long-range, developmentally regulated changes in H3 acetylation, and H3 acetylation status was tig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
192
1
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(206 citation statements)
references
References 32 publications
11
192
1
2
Order By: Relevance
“…2a), the transition to the DP stage was remarkably accompanied with a shift to a hyperacetylated state (Fig. 2b), as first noticed by McMurry and Krangel on TEA, J § 25 and C § [12]. We extended the study to histone H4 and the same global increase in the acetylation level was observed ( Fig.…”
Section: H3 and H4 Histone-tail Acetylation In The Tcr-j > Locus Priosupporting
confidence: 74%
See 3 more Smart Citations
“…2a), the transition to the DP stage was remarkably accompanied with a shift to a hyperacetylated state (Fig. 2b), as first noticed by McMurry and Krangel on TEA, J § 25 and C § [12]. We extended the study to histone H4 and the same global increase in the acetylation level was observed ( Fig.…”
Section: H3 and H4 Histone-tail Acetylation In The Tcr-j > Locus Priosupporting
confidence: 74%
“…For H4, the overall levels of acetylation were weaker than for H3 and no remarkable gradient could be revealed. In their pioneer study, McMurry and Krangel [12] showed that histone H3 is acetylated along the TCR § locus prior to the V § J § rearrangements (they used the RAG2-/-×tgTCR g model, similar to the RT3 model), However, the authors restricted their study to histone H3 and to one J § segment only (J § 25). Here we show that the acetylation of histone H4 is as remarkable as the acetylation of histone H3; furthermore the study of several J § segments along the J § cluster allows us to reveal a gradient of acetylation for H3, that mirrors the gradient of usage of the J § segments, with a maximum at the 5´end of the cluster where the first waves of rearrangements occur.…”
Section: H3 and H4 Histone-tail Acetylation In The Tcr-j > Locus Priomentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it has been demonstrated that demethylation of L chain genes occurs during B cell development, and is associated with onset of V(D)J recombination (Goodhardt et al, 1993;Mostoslavsky et al, 1998). More recently, several studies have demonstrated that loci active in V(D)J recombination contain nucleosomes with acetylated histone proteins (McMurry and Krangel, 2000;Chowdhury and Sen, 2001;Johnson et al, 2003), and that changes in histone acetylation are dynamic during B cell differentiation. Furthermore, acetylation of histones is not uniform throughout the V H locus, but is narrowly confined to promoters, coding regions and RSSs, with lower levels of histone acetylation in intergenic regions (Johnson et al, 2003;Espinoza and Feeney, 2005).…”
Section: Introductionmentioning
confidence: 99%